Hubungan Sikap Perawat Dengan Tingkat Kepuasan Pasien Rawat Inap Di Puskesmas Wilayah Sidoarjo - Fauziah Fitri Hernanto; Elfa Lailatul Izza (2019)
Health is the most value asset for life, therefore customer satisfaction is very important to be concerned. Customer satisfaction is a condition in which desire, expect and complaint were met, while the service is an action that met the other needs.The purpose of this research is to analyze the correlation nurse’s attitude and patient’s satisfaction. Research method is using analytic descriptive with cross-sectional approach. Population is hospitality stay patients and nurses at Public Health Service. Population size is 30 patients and 10 nurses. And taking-sample technique is using Non-probability sampling with Consecutive sampling approach. Data collection is using the questionnaire. The result is that 80% of the patients were less satisfaction over the service and description of unassertive of the nurse’s attitude (60%) with spearman correlation test  = .000 meaning that there is significant correlation. The conclusion is that nurse’s attitude in giving the service is able to influence of patient’s satisfaction. Keywords: Nurse’s attitude, patient satisfaction level